User Experience Evaluation at SIMARIS UPN Veteran Jatim (Module for reviewers) using the User Experience Questionnaire - Eka Dyar Wahyuni; Mohamad Irwan Afandi; Doddy Ridwandono; Anisa Rahma Salsabila (Future Science, 2022)
Aplication that are useful have a long lifespan, not just a year or two. To remain useful, applications must evolve/change, be it to facilitate changes to processes, policies or other requirements. These changes can be minor or major. One of the things that often changed is the user interface and user experience of the application, which greatly influences customer satisfaction. There are many methods to measure ux, one of them is UEQ. This study aims to measure the UX of SIMARIS users, so that this application has a long lifespan. SIMARIS is one of the applications at UPN “Veteran” Jawa Timur which is used to manage the implementation of internally funded research and social engagement activities. There are many modules in SIMARIS, one of them is the reviewer module which is used by reviewers to assess proposals, monev reports, and also final results of researchers. This research was conducted by distributing UEQ questionnaires to 10 reviewers. Based on the comparison with the benchmark scale, the results of the questionnaire related with attractiveness, clarity, efficiency, and novelty, the results are above average, while the results of accuracy and stimulation are good. These results indicate that SIMARIS is good, but efforts still need to be made to improve the attractiveness, clarity, efficiency, accuracy, stimulation and novelty by providing functions or features that help to get the job done faster and are fun to use.